Analisis Perbandingan Respon Dinamik Sistem Suspensi Semi-Aktif dengan Sistem Suspensi Dynamic Vibration Absorber (DVA) Semi-Aktif - Totok R. Biyanto; Yerri Susatio; Syamsul Hadi (Institute of Research and Community Outreach, Petra Christian University, 2014)
There are two important matters in the suspension system that must be concern, there are comfortable and stabilityof vehicle that provide or supported by the whole suspension system. Whereas passive suspension system design only concern with comfortable or stability of vehicle with pros and cons from that aspect respectively.In the active design, the two aspect can be achieved with minimize cons respectively. However active suspension in the application iso complex and high cost. Many research looking for the solution between two systems, one of them was using dynamic vibration absorber (DVA) and semi-active suspension. ISE, IAE, and ITAE are used for performance index to achieved optimum control gain from trial error tuning with 0,001 – 10 range. The result shows that Semi-active suspension system (SSSA) with gain = 3, can achievedmaximumovershoot reduction 28.29%, for gain = 4 maximum overshoot reduction 24.32%, and forgain = 7maximum overshoot reduction 18.61% compared to passive suspensionin step mode.